A Comparative Study of Biomimetic Synthesis of EDOT-Pyrrole and EDOT-Aniline Copolymers by Peroxidase-like Catalysts: Towards Tunable Semiconductive Organic Materials - Martínez-Cartagena, Manuel Eduardo; Bernal-Martínez, Juan; Banda-Villanueva, Arnulfo; Magaña, Ilse; Córdova, Teresa; Ledezma-Pérez, Antonio; Fernández-Tavizón, Salvador; Díaz de León, Ramón (Frontiers in Chemistry, 2022)
It has been two decades since biomimetic synthesis of conducting polymers were first reported, however, the systematic investigation of how catalysts influence the properties of the conducting polymers has not been reported yet. In this paper, we report a comparative study between peroxidase-like catalyst, dopants, and their effect on the properties of poly (3,4-ethylenedioxythiophene) (PEDOT), polypyrrole (PPY), and polyaniline (PANI). We also investigate the EDOT-Pyrrole and EDOT-Aniline copolymerization by enzymomimetic synthesis using two catalysts (Ferrocene and Hematin). It was found that, chemically, there are no detectable effects, only having small contributions in molar ratios greater than 0.7–0.3. Spectroscopic data provide solid evidence concerning the effect in the variation of the molar fractions, finding that, as the molar fraction of EDOT decreases, changes associated with loss of the conjugation of the structure and the oxidation state of the chains were observed. The electrical conductivity was considerably modified depending on the type of catalyst. Hematin produces conductive homopolymers and copolymers when doped with p-toluene sulfonic acid (TSA), while ferrocene produces low conductive copolymers under the same conditions. The mole fraction affects conductivity significantly, showing that as the EDOT fraction decreases, the conductivity drops drastically for both EDOT-PY and EDOT-ANI copolymers. The type of dopant also notably affects conductivity; the best values were obtained by doping with TSA, while the lowest were obtained when doping with polystyrene sulfonate (PSS). We also draw a biomimetic route to tailor the fundamental properties of conducting homopolymers and copolymers for their design and scaled-up production, as they have recently been found to have use in a broad range of applications.